The Questioning Gaze: on Ergy Landau’s photos taken in China - Fisli, Éva (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
Today, Ergy Landau (Budapest,1896 - Paris, 1967), a French-Hungarian photographer is rather known as an excellent photographer whose atelier was also an important meeting point for artists in interwar Paris. In my paper I would like to focus on a less known part of her carreer, namely on her travel to China in 1954. In the year following their visit, Landau and Goncourt Prize winner Pierre Gascard published two books about China. One of them was published under the title of "Chine ouverte". In this booklet the role of the photographs is not significant. However, the second book, "Aujourd'hui la Chine", prefaced by Claude Roy, is a carefully edited volume in which photos and texts mutually complete each other. In the 1950s, a growing number of texts by leading French authors documented the socio-political changes of China. The travel of Gascar and Landau followes the tendency of these travel reports. On the photos by Landau one can see the traces of the cultural transition, the changes of urban landscape, those of the fast insdustrialization and the mingling of times. The paper raises these questions: what might the Western reader of China actually see in 1954? How can we recognize the photographer's gaze on her photos? What is the connection between the vintage prints and the edited book? Into what kind of society the provides a glimpsee?